The Effect of Green Marketing toward the Consumers Buying Interest of Starbucks Coffee Mediated By Brand Image - Livia Windiana; Ary Bakhtiar; Via Rizky Kurniasih; Shaila Basamah (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2020)
Starbucks is a company applied to go green and concerned in the environment. Moreover, it is supported by the policy regarding the plastic cups minimalization and recycled materials used in Starbucks outlets. The objectives of the study are (1) To determine the effect of green marketing on Starbucks coffee brand image in Malang, (2) To determine the effect of brand image on buying interest in Starbuck Coffee in Malang. This research conducted at Starbucks Malang City Point and Starbucks Kota Araya in March-July 2019. The object of the research was the brand image (X1) green marketing (X2) and buying interest (Y). The data were analyzed using qualitative descriptive analysis, reliability test analysis, and path analysis. The results were (1) Green Marketing had positive and significant effects on Brand Image in other words the better quality of Green Marketing impacted on Brand Image quality improvement Starbucks Outlets in Malang (2) Brand Image had positive and significant effects on buying interest, in another sense better Brand Image of Starbucks Outlets in Malang impacted on consumer buying interest enhancement.